(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The article examines the main aspects of educational services that affect economic development, including accessibility, quality and innovation in the educational sphere. The key aspects discussed are the problems and challenges facing the educational system, such as the uneven distribution of educational resources, problems of financing and quality of educational services in remote regions, as well as the need to implement international educational standards. In conclusion, the importance of continuing reforms in the field of education is emphasized to improve the socio-economic situation of the country, raise the standard of living of citizens and integrate Uzbekistan into the global economy. Аннотация: В статье рассматриваются основные аспекты образовательных услуг, которые влияют на развитие экономики, включая доступность, качество и инновации в образовательной сфере. Ключевыми аспектами обсуждаются проблемы и вызовы, с которыми сталкивается образовательная система, такие как неравномерное распределение образовательных ресурсов, проблемы финансирования и качества образовательных услуг в удаленных регионах, а также необходимость внедрения международных образовательных стандартов. В заключение подчеркивается важность продолжения реформ в области образования для улучшения социально-экономического положения страны, повышения уровня жизни граждан и интеграции Узбекистана в мировую экономику.